In vitro multiplication of Coffea arabica F1 hybrid (S.2800) and its performance in the field - Muniswamy, B.; Sreenath, H.L.; Samuel, Stephen D.; Jayarama, J. (Journal of Plantation Crops, 2015)
See the pdf file here http://indsocplantationcrops.in/journal.php#